2002
DOI: 10.1046/j.1365-2958.2003.03288.x
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore‐mediated cell signalling in Pseudomonas aeruginosa: divergent pathways regulate virulence factor production and siderophore receptor synthesis

Abstract: SummaryUnder iron-limiting conditions, Pseudomonas aeruginosa produces a siderophore called pyoverdine. Pyoverdine is secreted into the extracellular environment where it chelates iron, and the resulting ferripyoverdine complexes are transported back into the bacteria by a cell surface receptor protein FpvA. Pyoverdine also acts as a signalling molecule inducing the production of three secreted virulence factors. Binding of ferri-pyoverdine to FpvA transduces a signal to the periplasmic part of the membrane-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
204
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(214 citation statements)
references
References 61 publications
5
204
0
2
Order By: Relevance
“…Upon binding to iron, the Fe-PVD-FpvA complex interacts with the periplasmic domain of FpvR, allowing the expression of the regulators PvdS (PA2426) and FpvI (PA2387). PvdS upregulates the production of ToxA, PrpL, and pyoverdine, whereas expression of FpvI generates a positive-feedback loop through increased production of the PVD receptor FpvA (9). Recently, Shirley and Lamont characterized an additional protein necessary for the transport and signaling cascade of Fe-PVD (178).…”
Section: Pyoverdinementioning
confidence: 99%
“…Upon binding to iron, the Fe-PVD-FpvA complex interacts with the periplasmic domain of FpvR, allowing the expression of the regulators PvdS (PA2426) and FpvI (PA2387). PvdS upregulates the production of ToxA, PrpL, and pyoverdine, whereas expression of FpvI generates a positive-feedback loop through increased production of the PVD receptor FpvA (9). Recently, Shirley and Lamont characterized an additional protein necessary for the transport and signaling cascade of Fe-PVD (178).…”
Section: Pyoverdinementioning
confidence: 99%
“…Up-and downregulation of extracellular enzymes by iron limitation has been described for different bacteria (Tokuda et al, 1998;Enard & Expert, 2000;Maunsell et al, 2006). Although in some cases this regulation is part of a more complex pathway related to virulence (Beare et al, 2003), the function of this association remains unclear. F. psychrophilum is able to degrade haemoglobin (Nematollahi et al, 2003); thus the production of certain proteases related to haemolysis could perhaps be regulated by the levels of iron.…”
Section: Phenotypic Characterization Of the Fp1033 Mutantmentioning
confidence: 99%
“…Sequence analysis of ORF BPSL1787 revealed that it encodes a predicted protein with similarity to PvdS, an ECF sigma factor from P. aeruginosa (AAB09714; 44% I, 60% S) (16). PvdS is involved in the transcriptional activation of the pyoverdin biosynthesis genes, as well as other genes encoding virulence factors such as the endoprotease PrpL and exotoxin A (4,26,38,39,67). We designated this gene mbaS (for malleobactin sigma factor).…”
Section: Vol 188 2006 Siderophore Synthesis and Transport In B Psementioning
confidence: 99%